Toxic Effects of Essential Oils of Elattaria Cardamomum L. And Lambda- Cyhalothrin on Tribolium Confusum (Duval) - Al-Sinjari, Sofyan H. Sedo; Al-Attar, Hani J. (Science Journal of University of Zakho, 2015)
Toxic effect of Lambda-cyhalothrin and essential oils of cardamom seeds of Elettaria cardamomum (L.), individually or in combination, on the larva, pupa and adult stages of confused flower beetle, Tribolium confusum, through the topical application were studied. The percentages of mortality of larval stage exposed to Lambda-cyhalothrin, at concentrations of 0.25, 0.35, 0.50 and 0.75 µl/ larva were 13.33, 20, 36.67 and 46.67 % respectively. While, the percentages of mortality of pupa stage at concentrations of 0.25, 0.35, 0.50 and 0.75 µl/ pupa were 13.33, 16.67, 26.67 and 43.33 respectively. For adults, exposed to Lambda concentrations of 0.25, 0.35, 0.50 and 0.75 µl/ adult were 10.0, 13.33, 23.33 and 40.0 respectively. The percentages of mortality of larvae exposed to cardamom oil at concentrations of 0.1, 0.3, 0.5 and 1 µl/ larva were 60, 76.67, 90 and 96.67% respectively, while the mortality of pupa exposed to concentrations of 0.1, 0.3, 0.5 and 1 µl/ pupa were 46.67, 63.33, 83.33 and 90 respectively. The percentages of mortality of the adults exposed to concentrations 0.1, 0.3, 0.5 and 1 µl/ adult were 43.33, 60.0, 76.67 and 83.33 respectively. The synergistic ratios for larvae, pupae and adults exposed to mixture 1 (0.03 µl / insect cardamom oil and different concentrations of pesticide ), were 2.01, 1.70 and 1.60, respectively, where as the synergistic ratios of larvae, pupae and adults exposed to mixture 2 ( 0.07 µl / insect cardamom oil and different concentrations of pesticide) were 2.61, 2.34 and 3.10, respectively. This indicates that a combination of cardamom seeds oil with different concentrations of the insecticide Lambda produced synergistic effects.